PROGRAM UNDERWEAR RULESUNTUK MENCEGAH KEKERASAN SEKSUAL PADA ANAK USIA DINI - JUSTICIA, RISTY (Jurnal Pendidikan Usia Dini, 2015)
Abstract: This article discusses the conceptual studies relating to the prevention of sexual abuse in early childhood through underwear program rules. Program rules underwear is a place for parents and teachers to teach how to provide sex education for early childhood as an effort to prevent the occurrence of sexual abuse in children. The good efforts to prevent sexual violence by people who are closest to the child, parents and teachers. Early childhood is an individual who has the true curiosity one of which is sexual knowledge. As for the topics that are presented in this article include several things, among others, the concept of early childhood sex education, sexual abuse in early childhood, early childhood sex education.. The authors in this article so that a parent can anticipate sexual abuse in early childhood, which may be giving out advice and efforts so that the child can keep his body of people who intend to poor children. In addition, the child can know the boundaries of others as well as touch guard against malicious behavior of the people around the child. Keywords: sex education, child abuse, early childhood